Artful wellness: Attending chamber music concert reduces pain and increases mood and energy for older adults. (February 2017) - Clements-Cortés, Amy
Highlights: Chamber music concerts offer benefits to older adults. Statistically significant changes in pain reduction pre- to post-test. Statistically significant changes in increased mood & energy pre-to post-test. Psychosocial benefits included: engagement, enjoyment, meaning, & connection. Music therapist consultation for performers was crucial in the success of concerts. Abstract: The purpose of this study was to examine the experience of providing professional chamber music to cognitively intact and cognitively impaired older adults in various long-term care and community settings. A total of 30 concerts involving 4 types of chamber music performances were prepared and offered to the participating facilities over a 6-month period. 3 participant groups were involved in the data collection: performing musicians, staff at the long-term care and community centres, and older adults. Data were collected via surveys of the 3 participant groups, pre- and post-tests of older adults, informal comments recorded by the researcher and/or musicians, and observations. Results from pre- and post- tests using paired t -tests indicate that pain was reduced, and energy and mood increased for the older adults each at the (p < 0.01) level. 4 large themes emerged from the survey and observation data and demonstrated that when attending the concerts, older adults experienced: engagement, enjoyment, and special moments with others; and connection and meaning were fostered. Additionally, it was found that some of the benefits extended to the performing musicians. Further research is implicated on the impact of choral experiences for older adults diagnosed with cognitive impairment.